Effect of Plant Growth Response of Ocimum species to Diverse Population Densities in Southern Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
A field study was conducted to evaluate the growth performance of Ocimum species at five population densities at the research farm of Agricultural Development Programme (ADP) Awka, Anambra State, The research was a 2 x 5 factorial experiment laid out in randomized complete block design (RCBD) which was replicated three times. Two species of Ocimum spp (Ocimum sanatum and Ocimum gratissium) represented the main factor while the sub-factor consisted of five population densities (60,000 plant/ha, 100,000 plant/ha, 200,000 plant/ha, 300,000 plants/ha and 400,000 plant/ha The nursery was done on 3rd of May 2021 while transplanting was done on the 29th of May 2021 at a plant spacing of 50 x 33.3cm, 50 x 10cm, 25 x 20cm, 33.3 x 10cm and 25 x 10cm. Data were collected on plant height (cm), number of leaves, number of branches, leaf area (cm2), stem girth (cm). Data collected were subjected to analysis of variance (ANOVA) using GENSTAT release 7.2DE Statistical software and means were separated using Fishers least significant difference (LSD). Plant density of 400,000 plants/h (25 x 10cm plant spacing) significantly improved biomass attribute of Ocimum gratissium and Ocimum Sanctum. While under the plant density of 300,000 plants/ha (33.3cm x 10cm plant spacing) gave best performance for the growth parameters measuerd. Ocimum sanctum grew more luxuriantly and performed better than Ocimum gratissimum; in all the growth parameters measured.
Keywords: Growth parametres; Ocimum gratissimum; Ocimum sanctum nursery; Plant population density